Urban rainwater utilization: A review of management modes and harvesting systems - Xu, Jiayi; Dai, Jiangyu; Wu, Xiufeng; Wu, Shiqiang; Zhang, Yu; Wang, Fangfang; Gao, Ang; Tan, Yanping (Frontiers in Environmental Science, 2023)
Due to the impact of climate change and rapid urbanization, issues around global urban flood control and water environment security have emerged as major global concerns. As a practical way to address these issues, exploitation of urban rainwater resources has become a worldwide hotspot for research and application. This paper 1) briefly examined the evolution of rainwater utilization management modes in advanced countries, 2) classified urban rainwater utilization measures from the utilization stages into three categories—source control, medium transmission, and terminal treatment, 3) summarized the advantages, disadvantages, and scope of the application of these measures, 4) reviewed the benefits, drawbacks, and application areas of these measures, and 5) conducted a quantitative analysis of their impact on rainwater pollution and flood control.